Nonlinear Numerical Investigation on Higher Harmonics at Lee Side of a Submerged Bar - D. Ning; X. Zhuo; L. Chen; B. Teng (Abstract and Applied Analysis)
The decomposition of a monochromatic wave over a submerged object is investigated numerically in a flume, based on a fully nonlinear HOBEM (higher-order boundary element method) model. Bound and free higher-harmonic waves propagating downstream the structure are discriminated by means of a two-point method. The developed numerical model is verified very well by comparison with the available data. Further numerical experiments are carried out to study the relations between free higher harmonics and wave nonlinearity. It is found that the nth-harmonic wave amplitude is growing proportional to the nth power of the incoming wave amplitude for weakly nonlinear wave condition, but higher-harmonic free wave amplitudes tend to a constant value for strong nonlinear wave condition.